Clear and Fuzzy Neighborhood Models of Wastewater Treatment - Smyrin, A.M; Sedukh, I.A (International Journal of Engineering and Technology, 2018)
The paper describes the definition of wastewater and their main types, shows the main components of the sewage treatment plant. The process of wastewater treatment is presented using clear and fuzzy dynamic neighborhood models, their comparative characteristics are given, and a conclusion is drawn.